A moralidade crítica: contribuições sobre a formação da moralidade na perspectiva da psicologia sócio-histórica - Fernandes, Eliane Pinheiro (2021)
The present study aims to contribute to the existing studies in the Psychology of Education field about the formation of moral values according to Socio-historical Psychology perspective. It is a theoretical research based on Historical-dialectical Materialism and therefore, using Marxist contributions in the philosophy field that investigate ethical and moral issue. In a literature review, few studies on the theme based on Socio-historical Psychology were found. As moral formation is closely related to education - in its broad and formal sense - we also sought investigations guided by Historical-critical Pedagogy, since it is based both on Historical-dialectical Materialism and on Vigotski, Luria, Leontiev and Elkonin’s theoretical contributions. Due to the undeniable importance of its contribution to the moral development understanding, a dialectical reading of piagetian theory is proposed – philosophical bases of his theory and psychology were analyzed. The thesis here is: morality is historical and social, and humans are not naturally selfish; according to its ethics, morality is qualitatively differentiated both in levels of development (anomy, morality of obedience and critical morality) and in its roots; critical morality is substantially distinct from the higher level according to the liberal conception (autonomous morality). Understanding ethics as a human production and, therefore, mediated, it is reaffirmed that there are radically liberal values and there are values aimed at human emancipation. Pointing out the difference between ethics, moral and morality, it is concluded that morality is the objectification of ethics, hence the importance of its formation. The dialectical unit that consubstantializes morality is self-regulation, imagination and thought by concepts. From this unit, six guiding principles are proposed for critical morality formation in the school environment, which are: a) Collective game is the child morality foundation; b) Thought by concepts is fundamental for critical morality formation; c) Ethical-political suffering strengthens the morality of obedience and limits the formation of critical morality; d) Conflicts resolution in relations between students is a social practice that contributes to the development of critical morality; e) Collaborative activities contribute to non-individualistic education and a sense of collectivity, essential for critical morality formation; f) Aesthetic experience contributes to critical morality formation. Finally, critical morality formation limits in school and the need to encompass the devir in the praxis aimed at human emancipation are pointed out